2020
DOI: 10.1021/acs.iecr.0c01345
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation on Interfacial Mass Transfer Mechanism for Rayleigh Convection in Hele-Shaw Cell

Abstract: To understand better the evolution of convective finger for Rayleigh convection confined in a gap with moderate width, we investigated the absorption of CO2 into water experimentally and numerically. A combined particle image velocimetry (PIV) and laser-induced fluorescence (LIF) method was used to measure simultaneously the instantaneous liquid velocity and solute concentration distributions in a Hele-Shaw cell. The process was then simulated using a 3D model with nonequilibrium interfacial boundary condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…However, it should be noted that their work considers an aperture of 3 mm and, therefore, will have considerably higher gap-induced flow behavior compared to our study. 29 As shown in Figure 7, the formation of nascent fingers throughout the experiment is observable, as evident by tiny oval-shaped regions with low color scale values at the gas− water interface.…”
Section: Qualitative Visualization For Cell a (Ra Number 86816mentioning
confidence: 78%
See 2 more Smart Citations
“…However, it should be noted that their work considers an aperture of 3 mm and, therefore, will have considerably higher gap-induced flow behavior compared to our study. 29 As shown in Figure 7, the formation of nascent fingers throughout the experiment is observable, as evident by tiny oval-shaped regions with low color scale values at the gas− water interface.…”
Section: Qualitative Visualization For Cell a (Ra Number 86816mentioning
confidence: 78%
“…Furthermore, the highly concentrated regions merge and keep moving vertically downward, clearly observable in Figure 7e,f. Similar patterns of concentration distribution were reported in the simulation of Zhang et al 29 Furthermore, their investigation in the gap direction showed a lower concentration boundary outside the convective fingers, which could be attributed to an effect of gap-induced dispersion. However, it should be noted that their work considers an aperture of 3 mm and, therefore, will have considerably higher gap-induced flow behavior compared to our study.…”
Section: Qualitative Visualization For Cell a (Ra Number 86816mentioning
confidence: 99%
See 1 more Smart Citation
“…Although such experiments do capture the effects of density-driven flow, electromigration effects are not involved. Other experimental studies of convective dissolution of gaseous CO 2 in aqueous solutions have been conducted in pressure-volume-temperature (PVT) cells (Yang and Gu, 2006), Hele-Shaw cells (Kneafsey and Pruess, 2010;Class et al, 2020;Zhang et al, 2020;Jiang et al, 2020;Teng et al, 2021), and 3D granular porous media (Mahmoodpour et al, 2020;Brouzet et al, 2022). Amarasinghe et al (2020) reviewed CO 2 dissolution experiments and performed experiments of convective dissolution of CO 2 in a Hele-Shaw cell and porous media under supercritical CO 2 conditions.…”
Section: Selected Experiments For Model Evaluationmentioning
confidence: 99%
“…But the fluid dynamic behaviors of bubbles are complex and have extracted many research efforts . Recently, the bubble rising process in the confined space of Hele-Shaw cells was investigated by a number of authors for its important background of process intensification, as the confined space can provide the process a larger surface area, higher interfacial mass transfer coefficient, and longer contacting time of the two phases . In a confined space, the bubble rising movement is usually accompanied by complex deformations and oscillations of its rising trajectory, which result in unstable wake and increase in fluid turbulence and significantly affects the mass transfer process.…”
Section: Introductionmentioning
confidence: 99%